Demonstration of a Concentrated Potassium Carbonate Process for CO2 Capture - Smith, K.; Xiao, G.; Mumford, K.; Gouw, J.; Indrawan, I.; Thanumurthy, N.; Quyn, Dimple; Cuthbertson, R.; Rayer, A.; Nicholas, N.; Lee, A.; da Silva, G.; et al. (American Chemical Society, 2014)
A precipitating potassium carbonate (K2CO3)-based solvent absorption process has been developed by the Cooperative Research Centre for Greenhouse Gas Technologies (CO2CRC) for capturing carbon dioxide (CO2) from industrial sources, such as power plant flue gases. Demonstration of this process is underway using both a laboratory-based pilot plantlocated at The University of Melbourne and an industrial pilot plant located at the Hazelwood Power Station in Victoria, Australia. The laboratory-scale pilot plant has been designed to capture 4-10 kg/h CO2 from an air/CO2 feed gas rate of 30-55 kg/h. The power-station-based pilot plant has been designed to capture up to 1 tonne/day CO2 from the flue gas of a browncoal-fired power station. In this paper, results from trials using concentrated potassium carbonate (20-40 wt %) solvent are presented for both pilot plants. Performance data (including pressure drop, holdup, solvent loadings, temperature profile, and CO2 removal efficiency) have been collected from each plant and presented for a range of operating conditions. Plant data for thelaboratory-scale pilot plant (including temperature profiles, solvent loadings, and exit gas CO2 concentrations) have been used to validate and further develop Aspen Plus simulations, in anticipation of further work involving precipitation and the industry based pilot plant.